Răspuns :
a) || x-2|+3|=6
| x-2 | +3=6
| x-2 | =6-3
| x-2 |=3
x-2=3
x-2=-3
x=5
x=-1
b) ((3^25:3^16:3^9)^2013+2^15:9^9:2^4):(-3)
((3^9:3^9)^2013+2^7+2^4):(-3)
(1^2013+2^3):(-3)
(1+8):(-3)=9:(-3)=-3
2. (-6)×(-2)/x =18:(-9)/-5-(-6)=
12/x=-2/-5+^
12/x=-2/1
-2x=12
x=12:(-2)
x=-6
| x-2 | +3=6
| x-2 | =6-3
| x-2 |=3
x-2=3
x-2=-3
x=5
x=-1
b) ((3^25:3^16:3^9)^2013+2^15:9^9:2^4):(-3)
((3^9:3^9)^2013+2^7+2^4):(-3)
(1^2013+2^3):(-3)
(1+8):(-3)=9:(-3)=-3
2. (-6)×(-2)/x =18:(-9)/-5-(-6)=
12/x=-2/-5+^
12/x=-2/1
-2x=12
x=12:(-2)
x=-6